The MSY concept in a multi-objective fisheries environment – Lessons from the North Sea. (July 2016) - Kempf, Alexander; Mumford, John; Levontin, Polina; Leach, Adrian; Hoff, Ayoe; Hamon, Katell G.; Bartelings, Heleen; Vinther, Morten; Stäbler, Moritz; Poos, Jan Jaap; Smout, Sophie; Frost, Hans; et al.
Abstract: One of the most important goals in current fisheries management is to maintain or restore stocks above levels that can produce the maximum sustainable yield (MSY). However, it may not be feasible to achieve MSY simultaneously for multiple species because of trade-offs that result from interactions between species, mixed fisheries and the multiple objectives of stakeholders. The premise in this study is that MSY is a concept that needs adaptation, not wholesale replacement. The approach chosen to identify trade-offs and stakeholder preferences involved a process of consulting and discussing options with stakeholders as well as scenario modelling with bio-economic and multi-species models. It is difficult to intuitively anticipate the consequences of complex trade-offs and it is also complicated to address them from a political point of view. However, scenario modelling showed that the current approach of treating each stock separately and ignoring trade-offs may result in unacceptable ecosystem, economic or social effects in North Sea fisheries. Setting FMSY as a management target without any flexibility for compromises may lead to disappointment for some of the stakeholders. To treat FMSY no longer as a point estimate but rather as a "Pretty Good Yield" within sustainable ranges was seen as a promising way forward to avoid unacceptable outcomes when trying to fish all stocks simultaneously at FMSY . This study gives insights on how inclusive governance can help to reach consensus in difficult political processes, and how science can be used to make informed decisions inside a multi-dimensional trade-off space. Highlights: Implementing MSY or MEY leads to a multi-dimensional trade-off space Ignoring trade-offs may result in unacceptable outcomes "Pretty Good Yield" may be a better concept than a pure MSY or MEY approach Inclusive governance and science can help to resolve trade-offs